Research on design of soft gripper by dielectric elastomer actuator based on quadrangular star honeycomb support - Yuanlin Guan; Ziyin Liu; Qi Cheng; Xixin Yang; Chunyu Yu; Yibo Cheng; Xunzhe Gu (PLoS ONE, 2026)
This study proposes a soft gripper with dielectric elastomer actuator (DEA) and 3D printing quadrilateral star honeycomb support due to the insufficient structural stiffness when grasping irregular objects. According to the bending requirement of the soft gripper and the electrostrictive properties of the dielectric elastomer (DE), a quadrangular star honeycomb structure with zero Poisson’s ratio is proposed as the supporting structure for the soft gripper to enhance its stiffness. The mechanical properties of the honeycomb structure were analyzed via the finite element method (FEM) to improve its stress and horizontal compression displacement. By discussing different parameters such as the pre-stretching ratio of the dielectric elastomer and the pre-compression displacement of the honeycomb structure, we analyzed their influence on the bending displacement performance of the soft gripper. The performance of the soft grippers was verified through both simulations and experiments. The improvement soft gripper, composed of two-layer of dielectric elastomer with a 300% pre-stretching ratio and a honeycomb structure subjected to 20 mm pre-compression, exhibits a bending displacement of 13 mm on a voltage of 5000 V and can grasp objects weighting 5 g.